Amplification and overexpression of HER-2/neu in invasive ductal carcinomas of the pancreas and pancreatic intraepithelial neoplasms and the relationship to the expression of p21(WAF1/CIP1) - Hermanová, M; Lukás, Z; Nenutil, R; Brázdil, J; Kroupová, I; Kren, L; Pazourková, M; Růzicka, M; Díte, P (Neoplasma, 2004)
Overexpression of HER-2/neu was described in pancreatic intraepithelial neoplasia (PanIN) and in invasive ductal adenocarcinoma of pancreas in a variable proportion of cases. The effects of HER-2/neu overexpression on mitogenic signalling and cell cycle progression were studied in breast luminal epithelial cells and mitogen activated protein kinase-dependent induction of p21(WAF1/CIP1) was found to be necessary for G1 phase progression. Overexpression of p21(WAF1/CIP1) was described as an early event in the development of PanIN by Biankin et al. (2001) and this finding was supported by our previous study that, moreover, did not confirm the possible role of activating K-ras mutations in the induction of p21(WAF1/CIP1) overexpression. Relationship between p21(WAF1/CIP1) expression and HER-2/neu status in PanIN lesions and ductal adenocarcinoma of the pancreas was investigated in our study. Expression levels of p21(WAF1/CIP1) and HER-2/neu were examined imunohistochemically and the amplification of HER-2/neu gene was evaluated by fluorescence in situ hybridisation in HER-2/neu overexpressing adenocarcinomas. Fourty nine pancreatic resection specimens from patients with invasive adenocarcinoma were included into the study. A large spectrum of PanIN lesions adjacent to the structures of infiltrating adenocarcinoma was also examined. The possible role of HER-2/neu in an induction of p21(WAF1/CIP1) overexpression was not confirmed and p21(WAF1/CIP1) overexpression seems to be HER-2/neu independent in pancreatic ductal adenocarcinoma according to our results. Increasing levels of HER-2/neu expression were demonstrated in pancreatic intraepithelial neoplasia and in 18.75% of pancreatic adenocarcinoma. The only 2 from 9 HER-2/neu overexpressing adenocarcinomas showed the amplification of HER-2/neu gene. Based on these results, the overexpression of HER-2/neu in pancreatic adenocarcinoma seems to be a result of increased transcription rather than gene amplification. Therefore HER-2/neu represents a good target for therapy of pancreatic adenocarcinoma only in isolated cases.
Keywords: Cyclin-Dependent Kinase Inhibitor p21; cykliny; Cyclins; duktální karcinom slinivky břišní; Cell Cycle; Pancreatic Neoplasms; Transcription, Genetic; Immunohistochemistry; buněčná diferenciace; lidé; nádory slinivky břišní; pankreas; imunohistochemie; Carcinoma in Situ; Receptor, ErbB-2; buněčný cyklus; G1 fáze; receptor erbB-2; genetická transkripce; Adenocarcinoma; inhibitor p21 cyklin-dependentní kinasy; adenokarcinom; Carcinoma, Pancreatic Ductal; G1 Phase; hybridizace in situ fluorescenční; Cell Differentiation; Pancreas; In Situ Hybridization, Fluorescence; karcinom in situ; Humans